2010
DOI: 10.1097/rli.0b013e3181ee6e06
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorinated Dendrimer-Based Nanotechnology Platform

Abstract: A novel fluorinated dendrimer-based nanotechnology platform in (19)F MRI and a new bifunctional DOTA chelate were prepared and characterized. We introduce 2 methods for reducing the (19)F longitudinal relaxation time: (a) Increasing the generation; (b) covalent and noncovalent introduction of Gd(III)-chelates. A new bifunctional Gd(III)-chelate is presented. The investigations of imaging on rats suggest potential importance of the dendrimers in (19)F MRI application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The perfluorocarbon particles are also considerably larger in size at (around 200 nm diameter) and are therefore likely to be limited to cell labeling studies. Recently, Huang et al (20) reported an approach related to that which is described here. They combined dendrimer nanoparticles with gadolinium chelates leading to some improvements in relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…The perfluorocarbon particles are also considerably larger in size at (around 200 nm diameter) and are therefore likely to be limited to cell labeling studies. Recently, Huang et al (20) reported an approach related to that which is described here. They combined dendrimer nanoparticles with gadolinium chelates leading to some improvements in relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…29 Alternatively, 7 was obtained as a triflate salt by alkylation of N -formylcyclen 37 with 3.3 equivalents of methyl bromoacetate, followed by removal of the formyl group. 30 Ester 8 was reportedly isolated in 72% yield after reaction of cyclen with 2.24 equivalents of ethyl bromoacetate in dichloromethane without an additional base. 38 More recently, Natrajan, et al, 39 prepared 8 in 63% yield as a hydrobromide salt by reaction of cyclen with 3.3 equivalents of ethyl bromoacetate in acetonitrile in the presence of sodium bicarbonate.…”
Section: Resultsmentioning
confidence: 99%
“…Higher field MRI systems are becoming more common, and the SNR increases with the increasing magnetic field. 51 Furthermore, increasing the fluorine load in contrast media increases the fluorine density and lowers the detection limit for fluorine particles, thus enabling high sensitivity imaging. These developments support the clinical translation of hybrid 1 H/ 19 F MR imaging and spectroscopy with fluorine contrast media.…”
Section: Emerging Clinical Fluorine Mr Applicationsmentioning
confidence: 99%